Many are called but few are chosen: the emergence of Latino congressional candidates. (7th August 2020) - Ocampo, Angela X.; Ray, John
ABSTRACT: Prior work has shown that Latino candidates do not under-perform compared to other candidates, and that Latino underrepresentation is a function of supply rather than demand (Juenke, Eric Gonzalez. 2014. "Ignorance Is Bias: The Effect of Latino Losers on Models of Latino Representation." American Journal of Political Science 58 (3): 593–603; Juenke, Eric Gonzalez, and Paru Shah. 2015. "Not the Usual Story: the Effect of Candidate Supply on Models of Latino Descriptive Representation." Politics, Groups, and Identities 3 (3): 438–453). Building on this work we investigate what factors influence the prospects of Latino candidates from the supply side. Examining candidate emergence from the supply side requires that we examine not only the winners and losers, but also those who could have entered a pool of candidates but did not. Using an original dataset of latent and primary candidates running for U.S. House seats from 2004 to 2014, we show that Latino candidacy at the pre-emergence stage is sensitive to potential challengers and that party elites under-support Latino candidates relative to others. Latinos are predicted to receive fewer endorsements than non-Latinos, and those endorsements influence candidates' chances of winning office. Our findings suggest that the poor integration of Latinos into partisan networks is largely responsible for their limited presence in candidate pools and elected office.